Air-conditioning control system for energy saving application - Mohd Shahrizad, Ab Hamid (2009)
The usage of antenna is widely developed almost everyday and it has become one of human’s need. In today’s world, the receiving parabolic antenna is almost commonly use in the world including this region. The purpose of this project is to design an Antenna Movement Controller by using stepper motor with PIC as the controller algorithm. The objective is to control maneuver the parabolic antenna with various and elevation angle. As a result, the antenna able to receive the signal that transmit by satellite from various position or direction. The methodology of implementation of this project could be categorized into software development and hardware design. The software development are base on PIC programming as the controller of the stepper motor. The hardware involves three stages which are keypad, PIC16F84A circuit and stepper motor. The operation of this project starting from the keypad enter the angle value. Then, the PIC receive the data to execute the program. The stepper motor maneuver to the desire direction. This project can be applied to the moving vehicle, portable antenna and etc.